2007
DOI: 10.1152/ajpregu.00260.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogens and selective estrogen receptor modulators on vascular reactivity in the perfused mesenteric vascular bed

Abstract: Mark CJ, Tatchum-Talom R, Martin DS, Eyster KM. Effects of estrogens and selective estrogen receptor modulators on vascular reactivity in the perfused mesenteric vascular bed. Am J Physiol Regul Integr Comp Physiol 293: R1969-R1975, 2007. First published September 19, 2007; doi:10.1152/ajpregu.00260.2007.-Estrogens and selective estrogen receptor modulators (SERMs), such as raloxifene (RAL) and tamoxifen (TAM), acutely relax arteries, but the long-term effects of estrogens and SERMs on vascular reactivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
(56 reference statements)
2
9
0
Order By: Relevance
“…SHR were exsanguinated by aortic puncture under isoflurane anesthesia. The superior mesenteric artery was cannulated and the gut removed as previous described (25). Briefly, the isolated mesenteric vascular bed (MVB) was constantly perfused (5 ml/min) and superfused (0.2 ml/min) using two separate pumps with modified Krebs-Henseleit (in mM: 118 NaCl, 4.7 KCl, 1.2 MgCl 2 ·6H 2 O, 1.0 NaH 2 PO4, 2.6 CaCl 2 ·2H 2 O, 25 NaHCO3, 11.1 glucose; 37°C; pH 7.35-7.45), oxygenated with a 95% oxygen-5% carbon dioxide gas mixture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHR were exsanguinated by aortic puncture under isoflurane anesthesia. The superior mesenteric artery was cannulated and the gut removed as previous described (25). Briefly, the isolated mesenteric vascular bed (MVB) was constantly perfused (5 ml/min) and superfused (0.2 ml/min) using two separate pumps with modified Krebs-Henseleit (in mM: 118 NaCl, 4.7 KCl, 1.2 MgCl 2 ·6H 2 O, 1.0 NaH 2 PO4, 2.6 CaCl 2 ·2H 2 O, 25 NaHCO3, 11.1 glucose; 37°C; pH 7.35-7.45), oxygenated with a 95% oxygen-5% carbon dioxide gas mixture.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Brandin reported that ovariectomy did not alter the mesenteric constrictor responses to norepinephrine in SHR (22). Previously we observed variable effects of estrogens on mesenteric vascular reactivity depending on the formulation of estrogen compounds administered to rats (25). Data concerning the effects of androgens on mesenteric vascular reactivity are relatively sparse.…”
Section: Introductionmentioning
confidence: 97%
“…Doses were adjusted to account for Δ 8 E1 and equilin being in its unconjugated form1, and to approximate the rat body weight equivalent of the 0.625 mg dose, which was used in the WHIMS and is what women are most commonly prescribed (Acosta et al, 2009b; Engler-Chiurazzi et al, 2009). The high doses for Δ 8 E1 and equilin were based on the only other available reports in the rat model using these hormones, wherein Δ 8 E1 decreased depolarization-induced cardiac synapse norepinephrine release, and equilin elevated vascular reactivity in the mesenteric vascular bed (Eskin et al, 2003; Mark et al, 2007). The medium doses of Δ 8 E1 and equilin were half of the high doses.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the effects of these SERMs in the vasculature remains limited and contradictory. Both exhibited positive effects on local blood flow in some (Leung et al, 2007) but not other (Mark et al, 2007) studies, and both tamoxifen and raloxifene increased the risk of venous thromboembolic events (Cuzick et al, 2003, Decensi et al, 2005). …”
Section: Introductionmentioning
confidence: 96%
“…The vasculature is clearly a target for estrogen (Ling et al, 2006; Miller and Duckles, 2008; Xing et al, 2009), and estrogens can directly affect vascular function (Li and Stallone, 2005; Li M., et al, 2008; Mark et al, 2007). Nevertheless, the precise effects of estrogen in the vasculature remain contradictory and controversial.…”
Section: Introductionmentioning
confidence: 99%